2018
DOI: 10.1080/13645706.2018.1442349
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted vs. laparoscopic and abdominal myomectomy for treatment of uterine fibroids: a meta-analysis

Abstract: Uterine fibroids are extremely common uterine neoplasms. However, whether robotic-assisted laparoscopic myomectomy (RALM) is superior to laparoscopic myomectomy (LM) or abdominal myomectomy (AM) is still debatable. Consequently, we aimed to compare the three currently major surgical techniques used in patients with uterine fibroids. We searched the PubMed, the Cochrane Library, MEDLINE, Embase, and Web of Science databases up to April 22, 2017. The meta-analysis included 20 studies involving 2852 patients. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 42 publications
5
25
3
2
Order By: Relevance
“…LM mainly uses the observation hole and the operation hole to understand the anatomical structure and the lesion, and completes the lesions removal under the guidance of the TV screen [38]. While the AM requires a long incision in the abdomen for direct vision, the trauma and the pulling force of related tissue during the AM are relatively large [39], hence the risk of complications is higher and the recovery is slower. It can be seen that the LM in patients with uterine fibroids has obvious advantages, which can promote the rapid recovery after surgery and enhance the safety of patients.…”
Section: Discussionmentioning
confidence: 99%
“…LM mainly uses the observation hole and the operation hole to understand the anatomical structure and the lesion, and completes the lesions removal under the guidance of the TV screen [38]. While the AM requires a long incision in the abdomen for direct vision, the trauma and the pulling force of related tissue during the AM are relatively large [39], hence the risk of complications is higher and the recovery is slower. It can be seen that the LM in patients with uterine fibroids has obvious advantages, which can promote the rapid recovery after surgery and enhance the safety of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the present study, EBL was higher in the RSSM group (210.1±162.2 vs. 161.4±158.7 mL, P=0.013) than in the LSSM group. It has been known that wristed instrumentation and the three-dimensional vision system in robotic systems make suturing more accurate and faster [16]. These advantages may lead to decreased blood loss during operation.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages may lead to decreased blood loss during operation. In fact, a meta-analysis [16] including 2,852 patients reported that EBL (weighted mean difference, -33.03; P=0.02) in robotic multi-site myomectomy was significantly less than that for laparoscopic myomectomy. On the other hand, our result was different.…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts results obtained by Kalogiannidis et al in 2010 [11] who reported the average blood loss for LM 246 ± 161 ml and 351 ± 219 ml for laparotomy group (p = 0.03) which was statistically significant. Also Wang et al [12] in 2018 in a meta-analysis: robotic-assisted vs. laparoscopic and abdominal myomectomy for treatment of uterine fibroids concluded that there was a significant less amount of blood in robotic assisted laparoscopic myomectomy compared to laparotomy myomectomy. The mean operation time (H) (mean ± SD) was 1.27 ± 0.13 for LM group which was significantly less than 2.05 ± 0.07 for AM group (p = 0.006) ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, Nicel et al in 2014 [7] reported longer operation time with laparoscopic myomectomy which was 148.33 ± 66.26 min compare with 102.75 ± 42.37 min which was statistically significant (p = 0.013) laparotomy myomectomy. Wang et al [12] in 2018 in a meta-analysis concluded that robotic assisted laparoscopic myomectomy had prolonged operation time compared to laparotomy myomectomy. In our study, the difference could be explained by the fact that much time was spent suturing the regions from which the fibroids were extracted and the abdominal wall in AM group and also surgeon dependent.…”
Section: Discussionmentioning
confidence: 99%